PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DALAM UPAYA PENURUNAN ANGKA KECELAKAAN KERJA PADA PT. SUMI INDO, KARAWANG - Taufan Gojali (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aim to getting illustration Occupational health and safety management systems (OHSMS) implementation in order to decrease accident number in PT. Sumi indo, Karawang. in OHSMS implementation, assign (Occupational health and safety) OHS organization as cooperation forum between employers and employees, which is occupational health and safety coaching committee (OHSCC). Observation using method OHSMS audit, getting satisfactory result of OHSMS implementation that is equal to 95.18% advanced level category. This is indicated by the determination of SHE policy and commitment is based of hazard identification and risk assessment, OHS planning, activity implementation, monitoring and evaluation of OHS performance, top management review and continual improvement toward OHS performance improvement. From OHS external audit, Company was implementing 92.17% on advanced category Of this implementation, getting decreasing of accident number from average 10 cases every year to be 2 case in 2017.